Fodor's essential Great Britain 2025 - Andrews, Robert, 1957-; Bruno, Nick; Coffey, Sally (Journalist) (Fodor's Travel, 2025)
"Whether you want to explore London, hike the Scottish Highlands, or marvel at Stonehenge, the local Fodor's travel experts in Great Britain are here to help! Fodor's Essential Great Britain guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time."--